2010
DOI: 10.3354/meps08503
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal trends in mortality and growth of cod and haddock larvae result in an optimal window for survival

Abstract: Changing climate and global depletion of fish stocks have added urgency to the centuryold quest to understand the factors controlling fish production. The leading hypotheses advanced to explain the large (orders of magnitude) inter-annual variability in recruitment of young fish emphasize rapid growth and a match to prey production in the first weeks after hatching, although avoiding predators may be of equal or greater importance. Here we show for 2 important North Atlantic groundfish (Atlantic cod Gadus morh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…However, comparative approaches face important hurdles because the potential advantages of the similarities of location and environmental variability can be trumped by the differences in behavior or life histories among focal species. For example, Georges Bank cod (Gadus morhua) and haddock (Melanogrammus aeglefinus), despite taxonomic closeness, demonstrated significant differences in growth and mortality rate and their relationship to environmental conditions (Buckley et al 2010;Mountain and Kane 2010). Although identifying the importance of the differences represents an advancement in knowledge, whether in the case of Georges Bank cod-haddock or in other regions (e.g., Möllmann et al 2005Möllmann et al , 2008, the sum of the differences can also limit the identification of common principles that can serve to explain variations year-class strength.…”
Section: Stochastic Simulationsmentioning
confidence: 99%
“…However, comparative approaches face important hurdles because the potential advantages of the similarities of location and environmental variability can be trumped by the differences in behavior or life histories among focal species. For example, Georges Bank cod (Gadus morhua) and haddock (Melanogrammus aeglefinus), despite taxonomic closeness, demonstrated significant differences in growth and mortality rate and their relationship to environmental conditions (Buckley et al 2010;Mountain and Kane 2010). Although identifying the importance of the differences represents an advancement in knowledge, whether in the case of Georges Bank cod-haddock or in other regions (e.g., Möllmann et al 2005Möllmann et al , 2008, the sum of the differences can also limit the identification of common principles that can serve to explain variations year-class strength.…”
Section: Stochastic Simulationsmentioning
confidence: 99%
“…In a recent study, Huwer et al (in press) utilized sRD measurements to identify Baltic cod larvae in poor nutritional condition within areas having low concentration of the preferred prey, Pseudocalanus acuspes. In the Northwest Atlantic, Buckley et al (2010) identified 'windows for survival' of Atlantic cod and haddock larvae based upon seasonal and inter-annual differences in larval RD condition and prey abundance. Voss et al (2006) utilized sRD measurements to reveal size-specific 'windows of survival' for Baltic sprat larvae that were linked to the availability of suitable prey.…”
Section: Perspectivementioning
confidence: 99%
“…The inclusion of seasonal variations in demographic rates increases the realism of population models, but is generally lacking in application for fish management despite its well-documented occurrence (Post & Parkinson 2001, Shoji & Tanaka 2007, Buckley et al 2010. The model presented here incorporates temperature-driven growth rate, mortality, and reproduction for a small fish species, Cyprinodon variegatus, and is used to compare projections using seasonally varying and constant parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal variation in natural mortality and reproduction is well documented for fish species (Nordlie 2000, Shoji & Tanaka 2007, Buckley et al 2010. With the exception of overwinter mortality for commercially important stocks (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation